Development of Qur’anic Literacy in Islamic Religious Education Learning: A Case Study at SMA Negeri 4 Pangkalpinang - Rofiqoh, Siti; Suparta; Dewi, Indah Kusuma (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the development of Qur’anic literacy within Islamic Religious Education learning at SMA Negeri 4 Pangkalpinang by examining how the program is institutionally designed, pedagogically implemented, and systematically evaluated to strengthen students’ reading competence and religious character formation in a public secondary school context. The research employed a qualitative field research design using a case study approach, with data collected through in-depth interviews, classroom and extracurricular observations, and document analysis of assessment records and institutional policies. Data were analyzed using the Interactive Model of Miles and Huberman, supported by triangulation to ensure credibility. The findings reveal that Qur’anic literacy development is structurally integrated into Islamic Religious Education learning rather than positioned as a supplementary activity, and is implemented through a differentiated pedagogical model consisting of foundational Iqra’-based instruction, drill reinforcement for fluency, and Tahfidz enrichment for advanced learners. The development process follows a cyclical framework involving diagnostic assessment, staged instruction, mentoring through peer tutoring, periodic evaluation, and literacy culture reinforcement practices such as One Day One Ayat and morning Tadarus. Evaluation mechanisms include placement, formative, diagnostic, and summative assessments through oral recitation tests, written examinations, and memorization deposits, enabling adaptive instructional adjustments and measurable student progression. The novelty of this study lies in conceptualizing Qur’anic literacy as a systemic pedagogical process embedded within formal Islamic Religious Education learning, demonstrating that effective literacy development emerges from the integration of institutional commitment, differentiated instruction, and continuous evaluation. The study contributes theoretically by proposing an institutional, differentiated, and adaptive model of Qur’anic literacy development, and practically by offering a structured framework for secondary schools seeking to strengthen religious literacy and character formation within formal educational settings.